Raman Responses in Mechanically Activated BaTiO3. Issue 2 (11th January 2014) - Pavlovic, Vera P.; Nikolic, Maria V.; Pavlovic, Vladimir B.; Blanusa, Jovan; Stevanovic, Suzana; Mitic, Vojislav V.; Scepanovic, Maja; Vlahovic, Branislav; Hoffman, M.
<x xml:space="preserve">Abstract</x> The structure and lattice dynamics of mechanically activated BaTiO3 was investigated in this study. Phonon behavior and crystal structure stability of the obtained nanocrystalline BaTiO3 were discussed from the view point of crystallite size effects and microstrains induced by mechanical activation. A systematic study of Raman responses indicates that mechanical activation has a distinct influence on BaTiO3 lattice spectra affecting the intensity, width, and position of Raman modes. The measured Raman spectra were deconvoluted and phonon parameters were estimated. It has been established that applied mechanical activation leads to a significant decrease in the mean crystallites size, but nevertheless enables formation of tetragonal nanocrystalline BaTiO3.